USING YOUTUBE TO IMPROVEEFL READING COMPREHENSION AMONG VOCATIONAL - Nuramah Hayikaleng; Subadrah Madhwa Nair; Hariharan N Krishnasamy (Proceedings of The ICECRS, 2016)
In Thailand, YouTube has not been widely used for educational purposes especially in Narathiwat. The purpose of this study was to investigate the effects of using YouTube on EFL reading comprehensionamong vocational students. A quasi-experimental design was adopted. Two groups of first year vocational students at Narathiwat Technical College were purposefully assigned to the experimental and the control groups. The instruments used in this study were pre-test and post-test. Students in the experimental group were taught reading comprehension using YouTube and the students in the control group were taught using conventional method. The results showed positive effects of using YouTube. Therefore, YouTube should be considered as an effective instructional tool for improving English reading comprehension and as an important teaching resource in English classrooms.